Reserva extrativista marinha de Cururupu: limites e possibilidades à sustentabilidade ambiental. - REIS, Rosalva de Jesus dos (2019)
There are analyzed the possibilities and limitations for environmental sustainability in the Marine Extractive Reserve of Cururupu, Conservation Unit established in 2004 and located in Maranhão west coast, set in the archipelago, where predominates the mangrove ecosystem, which supports local economic activities. This ecosystem is important for the reproduction and development of local species and is also important for migratory birds in their displacement between hemispheres. The traditional population that inhabits the RESEX dedicates predominantly to artisanal fisheries, economic activity wrapped in a series of political contradictions, socioeconomic and environmental. It makes an approach on environmental issues on Earth and in Brazil, to then address the specific issues of RESEX. There are explained the phenomena that led to discussions that substantiated from the century. XX to the present day and how Brazil was situated within this broader context. It is also approached the leads of the debate on environmental issues, globally and in Brazil. The methodological procedures used in the research were: data compatibility of Census 2000 and 2010, made available by the Brazilian Geography and Statistics Institute (IBGE) in the database aggregates by sectors Census, bibliographic and documentary research. There were made non-participatory observations and unstructured interviews with residents of the Reserve, representatives of local institutions such as Colônia de Pescadores, Sindicato de Pescadores and Associação de Moradores, with technicians of the managing organ and organs at the municipal level and the Capitania dos Portos do Estado do Maranhão (Appendix A). Data analysis took place from discourse analysis (Foucault, 2014) and field, habitus and capital conceptions, according to Bourdieu (1989 and 2004). For the recognition of environmental dynamics, direct observations were made, satellite images of comparisons of the early 2000s and the current decade; about RESEX, there were approached political processes and the interests that resulted in the creation of the protected area. From the reports and analysis of official documents, there were analyzed the contradictions inherent to the mentioned process. When RESEX‟s day-to-day was approached, there were discussed the fishing industry, the main generator of income in place and in which all the families are involved. There were analyzed the actions of various institutions which act or should act in RESEX. In interviews with local residents, the aim was to apprehend the perception that they have about the conservation unit and the managing organ.